Analysis of Multipurpose Credit (KMG) Procedures at Bank Sumut Syariah KCP Rantau Prapat - Nisa, Khairani; Ria Armayani Hasibuan, Reni (CV. Lafadz Jaya, 2022)
Banks are one of the state intermediaries to achieve the goals of the Indonesian nation. Therefore, the level of credibility or quality of the bank is very important and needs attention. This will certainly support public confidence in banking. This will influence and support public confidence in the existence of the bank. Therefore, the soundness of the bank is something that is important and requires attention. In general, banks are a means for the community to save or entrust money, banks can also provide and distribute assistance and act as intermediaries in transactions and payments. KMG targets are people who work as long-term employees and civil servants in an office/agencies/employee cooperatives/institutions/company so as to obtain guaranteed credit returns from the monthly income received by the employee.